Komparasi Mekanisme Transmisi Kebijakan Moneter Syariah dan Konvensional Melalui Jalur Harga Aset Terhadap Inflasi di Indonesia - Nikita Indi Kumala; Suherman Rosyidi (Universitas Airlangga, 2017)
The purpose of this study is to find out the effect of mechanism Sharia andconventional monetary policy transmission through asset prices on inflation in Indonesia during 2011-2015. The method used is quantitative analysis and the model used is OLS (Ordinary Least Square) to find out the effect in the long term and ECM Model (Error Correction Model) for short term. The data used is time series data with monthly data units during January 2011 to December 2015 period. This study uses the data from Bank Indonesia, the Central Bureau of Statistics (Badan Pusat Statistik), and the Financial Services Authority (Otoritas Jasa Keuangan). The results of this study shows that the syariah model shows significantly negative towards the inflation, and the conventional model shows not significantly towards the inflation.